2017
DOI: 10.1002/jmor.20727
|View full text |Cite
|
Sign up to set email alerts
|

The vocal sac of Hylodidae (Amphibia, Anura): Phylogenetic and functional implications of a unique morphology

Abstract: Anuran vocal sacs are elastic chambers that recycle exhaled air during vocalizations and are present in males of most species of frogs. Most knowledge of the diversity of vocal sacs relates to external morphology; detailed information on internal anatomy is available for few groups of frogs. Frogs of the family Hylodidae, which is endemic to the Atlantic Forest of Brazil and adjacent Argentina and Paraguay, have three patterns of vocal sac morphology-that is, single, subgular; paired, lateral; and absent. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 50 publications
(90 reference statements)
0
10
0
Order By: Relevance
“…Behavioral studies of diurnal anuran species of the genera Hylodes and Micrixalus have demonstrated that individuals direct their visual signals toward their conspecific receivers (Preininger et al 2013, de Sá et al 2016. Male Hylodes japi, for example, perform visual signals by using their double vocal sacs independently, inflating either the right or left vocal sac depending on the location of the target conspecific (de Sá et al 2016, Elias-Costa et al 2017. Similarly, male Micrixalus saxicola (Jerdon, 1853) coordinate the use of their forelimbs toward the position of a conspecific (Preininger et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral studies of diurnal anuran species of the genera Hylodes and Micrixalus have demonstrated that individuals direct their visual signals toward their conspecific receivers (Preininger et al 2013, de Sá et al 2016. Male Hylodes japi, for example, perform visual signals by using their double vocal sacs independently, inflating either the right or left vocal sac depending on the location of the target conspecific (de Sá et al 2016, Elias-Costa et al 2017. Similarly, male Micrixalus saxicola (Jerdon, 1853) coordinate the use of their forelimbs toward the position of a conspecific (Preininger et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These include unique types of lateral vocal sacs in Trachycephalus (Hylidae) and Pelophylax (Ranidae), paired subgular lobes in Hylodidae, Nannophryne + Euphlyctis + Hoplophryne (Dicroglossidae), and Gephyromantis (Mantellidae), and bilobate expansions in Triprion + Smilisca (Hylidae) and Spea (Scaphiopodidae), among others (see full list of synapomorphies in Appendix S6). Nevertheless, the other two components that make up the vocal sac (the internal mucosa and the gular skin) also are highly diverse, and their variation, which was not studied here, must necessarily be evaluated to properly assess the evolution of vocal sacs (Elias-Costa et al, 2017).…”
Section: Sexual Dimorphism and Relationship With The Vocal Sacmentioning
confidence: 99%
“…They consist of a thin elastic chamber derived from the buccal mucosa, enveloped externally by the IM and the IH, and the gular skin (Tyler, 1971a). The great morphological diversity of vocal sacs among anuran species is, in part, related to the disparity of the submandibular muscles that form its ventral wall (Liu, 1935;Tyler, 1971aTyler, , 1972Elias-Costa et al, 2017;Targino et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most families in the order anuran have inflatable gular skin, such as Hylidae , Eleutherodactylidae , and Leptopelis; however, the size, shape, and color can vary significantly between species [ 6 , 7 , 8 ]. Commonly associated with frogs is the single inflated gular skin located under the floor of the gular; however, some species can have two external vocal sacs or no external vocal sac at all [ 5 ].…”
Section: Introductionmentioning
confidence: 99%